2003
DOI: 10.1111/1467-9450.00324
|View full text |Cite
|
Sign up to set email alerts
|

The role of locomotion in the acquisition and transfer of spatial knowledge in children

Abstract: The role of locomotion in the acquisition and transfer of spatial knowledge was investigated in 144 five-, seven- and eleven-year-old children. Two experiments were conducted in the Kiel locomotor maze. In the first experiment, one group of children explored the spatial layout by walking through the maze, while another learned the maze by surveying the layout. In the second experiment, children were exposed to one of two orientation tests in the maze, one of which could be solved using "landmark orientation", … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 29 publications
4
39
0
Order By: Relevance
“…Herman concluded that traversing routes between landmarks within a spatial area is important for the development of cognitive maps and his findings have been cited in much of the subsequent work in the area (e.g., Foreman et al, 1990;McComas et al, 1997, among others) as indicating the benefits of active exploration in spatial learning. Consistent with this interpretation, Lehnung, Leplow, Ekroll, Herzog, Mehdorn and Ferstl (2003) found that when tested in the Kiel locomotor maze, which requires a participant to identify 5/20 floor-level lights as to-be-remembered targets, 5-11 year old-children could acquire considerable spatial information when viewing from the perimeter, but needed to experience locomotor exploration within the maze in order to make 9 "relational place orientation" judgements, i.e., to make judgements based upon a cognitive "map" of the experimental space.…”
Section: Introductionsupporting
confidence: 57%
“…Herman concluded that traversing routes between landmarks within a spatial area is important for the development of cognitive maps and his findings have been cited in much of the subsequent work in the area (e.g., Foreman et al, 1990;McComas et al, 1997, among others) as indicating the benefits of active exploration in spatial learning. Consistent with this interpretation, Lehnung, Leplow, Ekroll, Herzog, Mehdorn and Ferstl (2003) found that when tested in the Kiel locomotor maze, which requires a participant to identify 5/20 floor-level lights as to-be-remembered targets, 5-11 year old-children could acquire considerable spatial information when viewing from the perimeter, but needed to experience locomotor exploration within the maze in order to make 9 "relational place orientation" judgements, i.e., to make judgements based upon a cognitive "map" of the experimental space.…”
Section: Introductionsupporting
confidence: 57%
“…Note that other researchers have developed human analogs of the Water Maze (Astur et al, 1998;Astur et al, 2002;Jacobs et al, 1998;Lehnung et al, 2003;Leplow et al, 2003;Parslow et al, 2005). One way that our research differs from this previous research is that our primary focus was on cue-based bias, as predicted by our work from the dot location studies.…”
Section: Human Analog Of the Morris Water Mazementioning
confidence: 71%
“…While many researchers have utilized an analog to the Water Maze for studying spatial memory in humans (Astur, Ortiz, & Sutherland, 1998;Astur, Taylor, Mamelak, Philpott, & Sutherland, 2002;Jacobs, Thomas, Laurance, & Nadel, 1998;Lehnung, Leplow, Ekroll, Herzog, Mehdorn, & Ferstl, 2003;Leplow, Lehnung, Pohl, Herzog, Ferstl, & Mehdorn, 2003;Overman et al, 1996;Parslow, Morris, Fleminger, Rahman, Abrahams, & Recce, 2005), several alternative procedures have been developed. One extensively studied paradigm has been to have human subjects remember locations within a small two-dimensional field.…”
Section: Memory For Placementioning
confidence: 99%
“…Based on distributions of student responses, we compared students with travel times of 15 min or less v. more than 15 min to or from school. We examined differences in reporting between those who walked to school v. those with wheeled transport (cycling and motorized combined), as students walking to or from school would most likely be exposed to food-buying options due to increased contact time in the local area (56) .…”
Section: Covariatesmentioning
confidence: 99%